Investigation into the in vivo mechanism of diosmetin in patients with breast cancer and COVID-19 using bioinformatics - Wang, Jin; Ma, Shanbo; Li, Long; Chen, Yuhan; Yang, Qian; Wang, Feiyan; Zheng, Meiling; Miao, Shan; Shi, Xiaopeng (Frontiers in Pharmacology, 2022)
Patients with breast cancer are prone to SARS-CoV-2 infection (the causative virus of coronavirus disease [COVID-19]) due to their lack of immunity. Currently, there is no better treatment strategy for BRCA/COVID-19.In the current study, we examined the mechanism of action of Diosmetin, a flavonoid with anti-inflammatory properties, in patients with BRCA infected with SARS-CoV-2.We used bioinformatics technology to analyze the binding ability, biological function, and other biological characteristics of Diosmetin in vivo and examine the core target and potential mechanism of action of Diosmetin in patients with patients with breast cancer infected with SARS-CoV-2. A prognostic model of SARS-COV-2–infected breast cancer patients was constructed, and the core genes were screened out, revealing the correlation between these core genes and clinicopathological characteristics, survival rate, and high-risk and low-risk populations. The docking results revealed that Diosmetin binds well to the core genes of patients with breast cancer with COVID-19. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses suggested that Diosmetin inhibited inflammation, enhanced immune function, and regulated the cellular microenvironment in patients with BRCA/COVID-19. Moreover, 10 core targets were identified in patients with BRCA/COVID-19, including EGFR, PIK3R1, SRC, AKT1, AR, FYN, PTPN1, CDK1, APP and GSK3B. For the first time, we reveal the molecular functions and potential targets of Diosmetin in patients with breast cancer infected with SARS-CoV-2, improving the reliability of the new drug and laying the foundation for further research and development.